The fine line between normal and starburst galaxies. Issue 2 (14th July 2017) - Lee, Nicholas; Sheth, Kartik; Scott, Kimberly S.; Toft, Sune; Magdis, Georgios E.; Damjanov, Ivana; Zahid, H. Jabran; Casey, Caitlin M.; Cortzen, Isabella; Gómez Guijarro, Carlos; Karim, Alexander; Leslie, Sarah K.; et al.
Abstract: Recent literature suggests that there are two modes through which galaxies grow their stellar mass – a normal mode characterized by quasi-steady star formation, and a highly efficient starburst mode possibly triggered by stochastic events such as galaxy mergers. While these differences are established for extreme cases, the population of galaxies between these two regimes is poorly studied and it is not clear where the transition between these two modes of star formation occurs. We utilize the Atacama Large Millimeter/submillimeter Array observations of the CO J = 3–2 line luminosity in a sample of 20 infrared luminous galaxies that lie in the intermediate range between normal and starburst galaxies at z ∼ 0.25–0.65 in the Cosmic Evolution Survey field to examine their gas content and star formation efficiency. We compare these quantities to the galaxies' deviation from the well-studied 'main sequence' (MS) correlation between star formation rate and stellar mass and find that at log(SFR/SFRMS ) ≲ 0.6, a galaxy's distance to the main sequence is primarily driven by increased gas content, and not a more efficient star formation process.